Evaluating the long-term impact of antipoverty interventions in Bangladesh: An overview - Quisumbing, Agnes R.; Baulch, Bob; Kumar, Neha (International Food Policy Research Institute, 2011)
This paper provides an overview of a research project that assessed the long-term impact of three antipoverty interventions in Bangladesh—the introduction of new agricultural technologies, educational transfers, and microfinance—on monetary and nonmonetary measures of well-being. This paper begins by setting out the conceptual framework, methodology, and empirical methods used for the evaluation of long-term impacts. It discusses the context of the evaluations and the longitudinal data used. Key findings from the individual papers are then presented, followed by an indicative analysis of the cost-effectiveness of these interventions. The overview concludes with implications for programs and policy.